The Brachodidae of Sub-Saharan Africa (Lepidoptera, Cossoidea), with implications for the origin of the family - Kallies, Axel (Zootaxa, 2016)
Brachodidae are a small family of day-flying, rarely collected cossoid moths. Here, the Brachodidae fauna of Sub-Saharan Africa and the neighboring Arabian Peninsula is reviewed with special attention to the species of the subfamily Brachodinae. The origin of the African Brachodinae and their relationship to the Palaearctic genus Brachodes are discussed, and a Gondwanan origin of the family Brachodidae sensu stricto is proposed. A total of 34 brachodid species are considered in this study, most of which are figured. Two new genera, Archaeotychia gen. nov. (type species Atychia quiris Felder & Rogenhofer, 1875) and Nothobrachodes gen. nov. (type species Atychia infanda Meyrick, 1920) are described. Furthermore, 12 species are described as new to science: Archaeotychia semicuprea sp. nov., Archaeotychia dicksoni sp. nov., Archaeotychia khoisanorum sp. nov., Archaeotychia krooni sp. nov., Archaeotychia dentata sp. nov., Phycodes nigeriana sp. nov., Nigilgia scoblei sp. nov., Nigilgia agassizi sp. nov., Nigilgia ruwenzoriensis sp. nov., Nigilgia megabella sp. nov., Nigilgia arcana sp. nov. and Nigilgia crocea sp. nov. Moreover, Atychia metaspila Meyrick, 1926 syn. nov. is established as a new synonym of Archaeotychia albiciliata (Walsingham, 1891), and Atychia nycteropis Meyrick, 1920 syn. nov. as a new synonym of Nothobrachodes infanda (Meyrick, 1920). Atractoceros xanthoprocta (Meyrick, 1914) is transferred to the subfamily Phycodinae.